Microsurgical approach for unusual and unexpected malignant fibrous histiocytoma of the forearm: A case report - D'ORAZI, VALERIO (Mol Clin Oncol, 2015)
Soft tissue sarcomas are rare tumors with a dismal prognosis. Among the most common histological types of sarcomas of the extremities, malignant fibrous histiocytoma (MFH) is the one with the highest incidence. Surgery is considered to be the first choice of treatment for MFH. To the best of our knowledge, this is the first case report in the literature of a patient with MFH within the abductor pollicis longus (APL) muscle. This unusual location was also unexpected by the treating surgeons, as the preoperative magnetic resonance imaging localized the tumor inside a different muscle. A 79-year-old Caucasian man presented with a swelling in the middle third of the dorsal aspect of the left forearm. MFH was diagnosed following biopsy and instrumental diagnostic examinations. Surgical excision and simultaneous reconstruction was performed by the same microsurgical team, achieving an excellent functional outcome. The present case highlights the significance of microsurgical approach for improving strategic planning in oncologic surgery. Accurate surgical dissection, performed by a team of microsurgeons, allowed for the identification of the unusual and unexpected tumor localization within the APL muscle. For this reason, a change of surgical strategy allowed for preservation of the extensor digitorum communis muscle, which would otherwise have to be resected, with tendon transfer and successful restoration of the thumb abduction function.